The MHD flow of liquid film in the presence of dissipation and thermal radiation through an unsteady stretching sheet by HAM - et.al, C.N.Guled, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper examines the impact of magnetohydrodynamic (MHD) over a thin film of an unsteady stretching sheet. Prandtl number model of dynamic viscosity and thermal conductivity is examined using Homotopy analysis method. By Makinguse of appropriate self-similar conversion, the system of model partial differential equations (PDEs) with strong nonlinearity is converted into a non-dimensional set of couple ODEs (Ordinary Differential Equations). Consequently, the system of these transformed equations is analytically explained by implementing Homotopy Analysis Method (HAM). The effects of embedded parameters such as magnetic parameter (M), radiation parameter Nrand Eckert number (Ec) on involved distributions are interpreted graphically to examine the heat transport features for both sorts of unsteadiness parameters S=0.8 and S=1.2. Moreover, the (Cf) skin friction along with the (Nu) heat transport rate (Nusselt number) is formulated for different values of relevant variables.